Little Old Ladies’ Heart - Mengden, Thomas; Weber, Thomas (DMW - Deutsche Medizinische Wochenschrift, 2019)
The term “ventricular-arterial coupling” (va-coupling) describes the close interaction of the left ventricle with the arterial system during systole. Increased arterial stiffness in conditions such as isolated systolic hypertension (ISH) or increases in pulse wave reflection may lead to disturbed va-coupling. Pathological pulse wave reflection is closely related to increased left ventricular late systolic load, diastolic dysfunction and, in the long-term, the risk of new-onset HFpEF. Non-invasive technologies for pulse wave analysis may identify patients at increased risk for the development of diastolic dysfunction or HFpEF. Women are approximately two times more likely than men to develop HFpEF which may be explained by sex differences in cardiovascular pathophysiology. Elderly women with ISH show sex-specific alterations of pulse wave reflection, LV remodelling and va-coupling which may increase the risk of HFpEF.
Keywords: Pulswellenanalyse; ventrikulo-arterielles Coupling; isolierte systolische Hypertonie; geschlechtsspezifische Unterschiede